Pendidikan Kewarganegaraan dalam Program Sekolah Ramah Anak: Kajian Literatur Terhadap Hubungan dengan Pencegahan Bullying - Siska Damayanti; Karim Suryadi; Sri Wahyuni Tanszhil (UNIVERSITAS SLAMET RIYADI, 2024)
Civic Education plays a crucial role in shaping students' character and has a positive impact on the school environment. This research aims to reflect on the relationship between the implementation of Civic Education in child-friendly school programs and efforts to prevent bullying. The study aims to analyze the extent to which the integration of Civic Education in child-friendly schools can contribute to reducing bullying behavior among learners. This research is based on a qualitative approach, using the literature review method. The literature review was conducted through the analysis of scholarly papers, books, and relevant documents highlighting the role of Civic Education in character development, the promotion of citizenship values, and its connection to bullying prevention in the school environment. The results of the study indicate that the correlation between civic education and efforts to prevent bullying can be observed in various aspects, including goals, curriculum content, and the approaches and strategies of Civic Education teaching methods. Civic Education in the context of Child-Friendly Schools can help shape positive character and prevent bullying behavior. Keywords: Civic Education, Child-Friendly School, Bullying.